CHALLENGES FACED BY UZBEK COMPANIES IN FREIGHT TRANSPORTATION: ANALYSIS IN DOMESTIC AND INTERNATIONAL CONTEXT - Abdulatif A. Meliboyev; Z. M. Khametov (Modern American Journals, 2025)
Freight transportation plays a vital role in Uzbekistan’s economic development, facilitating the movement of goods across domestic regions and international markets. However, Uzbek transport companies face a multitude of challenges that hinder operational efficiency and competitiveness. This paper analyses these challenges in both domestic and international contexts, including infrastructure limitations, outdated logistics technologies, regulatory inconsistencies, and financial constraints. On the domestic front, road and rail networks often lack adequate maintenance, leading to increased transit times and cargo damage. Internationally, border crossing inefficiencies, non-harmonized customs procedures, and limited access to global logistics corridors pose significant barriers. The research employs qualitative and quantitative data to identify structural, technological, and policy-related constraints affecting freight operators. Recommendations are offered to improve transport policy, integrate digital logistics platforms, and enhance regional cooperation, especially under frameworks like the Central Asia Regional Economic Cooperation (CAREC) program. Addressing these barriers is essential for improving Uzbekistan’s trade competitiveness and attracting foreign investment in logistics infrastructure.
Keywords: Uzbekistan, freight transportation, logistics, domestic transport, international trade, infrastructure, customs, regulatory challenges, CAREC, transport policy.